A regulação em favor de investimentos privados em infra-estrutura - Kujawski, Fabio Ferreira (2007)
Issues concerning private investment in infrastructure projects, all over the world, are always very challenging. There are many reasons for this, since infrastructure projects depend on the conjoining of a variety of factors that must be present simultaneously, so that the sensitive private interest can be secured for projects of such complexity and often of a long-term and capital intensive nature. We intend to show that a country's success or failure in attracting private investment in infrastructure projects depends largely on there being a stable regulatory environment, administrative efficiency and trust in relations between the government and the private parties